An analysis of partnership models for environmental education in the primary and secondary schools in Phnom Penh - Sao Sambat Morakath; Perera, L.A.S. Ranjith; Amin, A.T.M. Nurul; Thapa, Gopal B.; Canada (CIDA) (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Improving knowledge about environment is an integrated of school education curriculum in more developing countries which pursue sustainable development goals. However, due to lack of collaboration and coordination among main partners, and limited civil society involvement with schools, Environmental Education in Cambodia is seen inadequate for this purpose. This study aims to examine the effectiveness of different partnership models to address the needs of Environmental Education in the capital city of Cambodia, Phnom Penh. The research focuses on key partners who are actively linked with schools viz; government agencies, International Non-Government Organizations, and Cambodian Non(S1(BGovernment Organizations. To analyze the effectiveness of partnership models, the study conducts a needs assessment at schools and compares these needs with what is provided through partnerships. The study finds that the major problems affecting Environmental Education in Phnom Penh as; insufficiently trained teachers, inadequate teaching and learning material, insufficient financial support and inadequate teaching time. The study also finds that two partnership models exist in supporting Environmental Education in Phnom Penh. A linear partnership model is used to disburse funds and resources that donor agencies provide to schools through government agencies. A triangular partnership model is used to train teachers and provide learning materials that International Non-Government Organizations or Cambodian Non-Government Organizations provide to the schools in collaboration with government agencies. The study finds that lack of monitoring and insufficient financial support; as major drawbacks of linear partnership model. Meanwhile, in the triangular partnership model, lack of partnership agreement, lack of common vision among partners and difficult administrative system among partners are found to be the drawbacks. The study concludes that triangular partnership model is more effective in catering the schools' needs. The study suggests that confirmation of builds partners' commitment and enforcement of the partnership agreement are the main factors to strengthen partnerships
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science Urban Environmental Management
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Environmental education -- Cambodia -- Phnom Penh; Education, Primary -- Cambodia -- Phnom Penh; Education, Seconary -- Cambodia -- Phnom Penh